PSYCHOLOGICAL CHARACTERISTICS OF THE SOCIAL PERCEPTION OF WORKS OF ART BY TEENAGERS - Zokirova , Sarvinoz O‘tkir qizi (Innovative Development in Educational Activities, 2024)
In this article, the nature of relationships related to teenagers, art and psychology is theoretically analyzed through the literature of foreign countries and nationals, and the negative changes that occur in the psychology of teenagers and their causes are studied. Attention was paid to the influence and connection aspects of psychology, including the psychology of adolescents.